Biomechanical asymetries and spinal loading in elit rowers with and without low back pain - Steenman, K.; Wielaard, K.; Lezeman, H.; Hofmijster, M.; Faber, G.; Dieen, J. (British Journal of Sports Medicine, 2014)
Background: Being the first most common site for injury in junior elite (24.2%) and elite rowers (31.8%), low back pain (LBP) prevalence is still increasing. Of the rowers with LBP, 15.8% report LBP to be the reason to end their rowing careers. However, the exact extent of the factors associated with this problem is not well understood, making management and prevention of LBP in elite rowers difficult. Objective: The aim of this study was to establish whether spinal loading, mediolateral seat drift, and asymmetry in force generation between left and right legs during an incremental rowing performance was more prominent in rowers with a history of low back pain (LBP) as compared to a control group of rowers without LBP. Design: Cross-sectional study. Setting: Laboratory setup, elite rowers. Patients: This study examined forty-two elite rowers (21 with a history of LBP; 21 without). Risk factor assessment: A 3-D motion analysis system was used during an incremental protocol on an instrumented rowing ergometer to measure spinal loading, mediolateral seat drift, and left-right leg force generation. Main outcome measurements: Mediolateral seat drift in millimeters, spinal loading in Newton and difference between left and right leg force generation in Newton. T-test and Man Whitney U tests where used to compare data of the two groups. Results: Significant differences in mediolateral seat drift were shown between groups in the first two steps of the protocol (step 1: U:130 Z:-2.277 with P=.023; step 2: U:116 Z: -2.629 with P=.09). No significant difference was found in spinal loading or left-right leg force generation. Conclusions: The greater mediolateral seat drift in rowers with a history of LBP is a start for preventing en managing LBP in elite rowers. But first, future research should focus on the origin of this mediolateral seat drift.